VD_FINDINFO Plainte / 2017 / 15 vom 15. Juni 2017 - VD Tribunal cantonal (2017)
DROIT D'ÊTRE ENTENDU, PROCÉDÉ TÉMÉRAIRE, CONDITIONS DES ENCHÈRES, PLAINTELP | 29 al. 2 Cst., 134 LP, 18 al. 1 LP, 20a al. 2 ch. 5 LP, 117 let. b CPC (CH)